A Marxist Critique of Power and Social Class in The Great Gatsby - Mauliana Tri Rusmawati; Ruly Indra Darmawan (Universitas Islam Negeri Palopo, 2026)
This study analyzes how F. Scott Fitzgerald uses the class contrast between Jay Gatsby and Tom Buchanan in The Great Gatsby to critique capitalist power and social class structures. This study employs a descriptive qualitative method using text analysis techniques to examine words, phrases, sentences, and dialogues obtained through close reading. The analysis is grounded in Karl Marx’s Marxist theory, particularly the concepts of class struggle, capital accumulation, and ideological domination. The results of the study indicate that Fitzgerald constructs a sharp contrast between old money and new money through spatial division (East Egg and West Egg), differences in the sources of wealth (inheritance and self-made wealth), ideological superiority, and unequal social consequences. Although Gatsby possesses significant economic capital, he lacks the social legitimacy and structural power of Tom Buchanan. These findings show that the dominant class maintains its position not only through wealth ownership but also through inherited privileges, social recognition, and control over ideological norms. In contrast, individuals from the emerging class remain vulnerable to exclusion. Furthermore, the contrasting fates of the two figures highlight the structural protection afforded to the elite class. This study also demonstrates that interpersonal conflict serves as a micro-level representation of capitalist power, thereby revealing the limitations of social mobility within the capitalist system.